2016
DOI: 10.1038/modpathol.2016.94
|View full text |Cite
|
Sign up to set email alerts
|

Pattern classification of endocervical adenocarcinoma: reproducibility and review of criteria

Abstract: Previously, our international team proposed a 3-tiered pattern classification (Pattern Classification) system for endocervical adenocarcinoma of the usual type that correlates with nodal disease and recurrence. Pattern Classification- A have well demarcated glands lacking destructive stromal invasion or lymphovascular invasion (lymphovascular invasion), Pattern Classification- B show localized, limited destructive invasion arising from A-type glands, and Pattern Classification- C have diffuse destructive strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 41 publications
1
29
0
4
Order By: Relevance
“…49 Another study showed an overall concordance of 74% with kappa values of 0.54, 0.32 and 0.59 for patterns A, B and C, respectively. 56 Kappa values improved when comparing binarised patterns (A versus B and C). 49,51 This system is applicable to all resections, as invasion pattern on cones and loop electrosurgical excision procedures (LEEPs) can predict invasion pattern on a subsequent hysterectomy, particularly in patterns B and C tumours.…”
Section: S I L V a P A T T E R N -B A S E D C L A S S I F I C A T I Omentioning
confidence: 95%
See 1 more Smart Citation
“…49 Another study showed an overall concordance of 74% with kappa values of 0.54, 0.32 and 0.59 for patterns A, B and C, respectively. 56 Kappa values improved when comparing binarised patterns (A versus B and C). 49,51 This system is applicable to all resections, as invasion pattern on cones and loop electrosurgical excision procedures (LEEPs) can predict invasion pattern on a subsequent hysterectomy, particularly in patterns B and C tumours.…”
Section: S I L V a P A T T E R N -B A S E D C L A S S I F I C A T I Omentioning
confidence: 95%
“…Several studies have demonstrated this 3‐tiered system to be reproducible among pathologists, with the reported kappa values ranging from fair to almost perfect ( k = 0.24–0.84) and moderate ( k = 0.65) . Another study showed an overall concordance of 74% with kappa values of 0.54, 0.32 and 0.59 for patterns A, B and C, respectively . Kappa values improved when comparing binarised patterns (A versus B and C) …”
Section: Classification Of Endocervical Adenocarcinomamentioning
confidence: 98%
“…Alternative classification systems incorporating stromal invasion pattern have been proposed for adenocarcinoma. [32][33][34] These systems remain to be validated for clinical use.…”
Section: Surgical Stagingmentioning
confidence: 99%
“…This principally subdivides EAC into prognostically relevant and reproducible HPV‐associated (HPVA) and non‐HPV associated (non‐HPVA) histological types . The second proposal, also of prognostic importance, is to replace the conventional, poorly defined grading systems that have low reproducibility with a pattern‐based classification . This only applies to HPVA EAC, as all non‐HPVA EAC fall into the poorest prognosis pattern C category.…”
Section: Cervical Adenocarcinomas With Ovarian Metastases Simulating mentioning
confidence: 99%
“…[99][100][101] The second proposal, also of prognostic importance, is to replace the conventional, poorly defined grading systems that have low reproducibility with a pattern-based classification. [102][103][104] This only applies to HPVA EAC, as all non-HPVA EAC fall into the poorest prognosis pattern C category. The incorporation of these two approaches into clinical management algorithms requires development and prospective evaluation through international collaborative projects.…”
Section: Cervical Adenocarcinomas With Ovarian Metastases Simulating mentioning
confidence: 99%